2022
DOI: 10.3390/biomedicines11010028
|View full text |Cite
|
Sign up to set email alerts
|

The Endocannabinoid System as a Target for Neuroprotection/Neuroregeneration in Perinatal Hypoxic–Ischemic Brain Injury

Abstract: The endocannabinoid (EC) system is a complex cell-signaling system that participates in a vast number of biological processes since the prenatal period, including the development of the nervous system, brain plasticity, and circuit repair. This neuromodulatory system is also involved in the response to endogenous and environmental insults, being of special relevance in the prevention and/or treatment of vascular disorders, such as stroke and neuroprotection after neonatal brain injury. Perinatal hypoxia–ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 190 publications
0
6
0
Order By: Relevance
“…Several studies have shown that the activation of cannabinoids has various advantages, such as neuroprotective effects [ 69 ]. More than 120 types of phytocannabinoids exist in hemp, but most studies have focused on CBD and THC [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the activation of cannabinoids has various advantages, such as neuroprotective effects [ 69 ]. More than 120 types of phytocannabinoids exist in hemp, but most studies have focused on CBD and THC [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Four review articles in this Special Issue summarize information on a wide array of topics related to cannabinoids. Duranti and collaborators review the current literature on the endocannabinoid system with regard to neuroprotection and neuroregeneration [ 18 ]. The focus of their review highlights the potential of modulating the endocannabinoid system to treat hypoxia–ischemia in newborns, which can lead to encephalopathy, a condition for which there are currently limited treatment options.…”
Section: Review Articles Brief Reports and Systematic Reviewsmentioning
confidence: 99%
“…The exhaustive description of ECS architecture and functioning is beyond the scope of this work; more details can be found elsewhere [24,25]. The right functioning of the ECS In a randomized, double-blind controlled clinical trial, CBD exerted antipsychotic properties comparable to the reference drug amisulpride [20,21].…”
Section: Endocannabinoid Systemmentioning
confidence: 99%
“…The exhaustive description of ECS architecture and functioning is beyond the scope of this work; more details can be found elsewhere [24,25]. The right functioning of the ECS is related to the natural balance established between its main components, which are CBRs, the endogenous ligands binding them, and the enzymes involved in the synthesis, transport, and degradation of ECs.…”
Section: Endocannabinoid Systemmentioning
confidence: 99%